2021
DOI: 10.3390/biom11070987
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell-Based Regeneration and Restoration for Retinal Ganglion Cell: Recent Advancements and Current Challenges

Abstract: Glaucoma is a group of irreversible blinding eye diseases characterized by the progressive loss of retinal ganglion cells (RGCs) and their axons. Currently, there is no effective method to fundamentally resolve the issue of RGC degeneration. Recent advances have revealed that visual function recovery could be achieved with stem cell-based therapy by replacing damaged RGCs with cell transplantation, providing nutritional factors for damaged RGCs, and supplying healthy mitochondria and other cellular components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…The neuroprotective paradigm is now well accepted, and many drugs and food-derived agents have shown efficacy in cell-based and animal model-based systems. Likewise, gene- [51,99] and cell-therapy [70,[100][101][102] and DOI: http://dx.doi.org/10.5772/intechopen.108914 Optic Nerve and Retinal Ganglion Cell Protection, Rejuvenation, and Regeneration… controlled electrical stimulation [92] and photobiomodulation [97,102] have beneficial effects and a place in tackling degenerative maladies. The latter alone, or coupled with optogenetic [102], photoswitch [103], electromagnetic, and ultrasound-based technologies [104,105], is also beginning to show promise in promoting cytoprotection and even potential axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprotective paradigm is now well accepted, and many drugs and food-derived agents have shown efficacy in cell-based and animal model-based systems. Likewise, gene- [51,99] and cell-therapy [70,[100][101][102] and DOI: http://dx.doi.org/10.5772/intechopen.108914 Optic Nerve and Retinal Ganglion Cell Protection, Rejuvenation, and Regeneration… controlled electrical stimulation [92] and photobiomodulation [97,102] have beneficial effects and a place in tackling degenerative maladies. The latter alone, or coupled with optogenetic [102], photoswitch [103], electromagnetic, and ultrasound-based technologies [104,105], is also beginning to show promise in promoting cytoprotection and even potential axonal regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…While promising, there are still many hurdles in terms of the duration of survival of the transplanted cells and the durability of their function in terms of vision restoration and the quality of the latter. Nevertheless, there is hope that further progress will be made such that translation of these laboratory findings to the glaucoma patients clinically can be achieved in the near future [69][70][71].…”
Section: Cell-replacement Therapies For Glaucoma Treatmentmentioning
confidence: 99%
“…Stem cell therapy aims to treat glaucoma through multiple mechanisms. Several preclinical studies reveal that stem cells can restore TM structure and function, directly replace RGCs, and increase RGC survival via secretion of neuroprotective and anti-inflammatory factors [52 ▪ ,53 ▪ ,54 ▪ ]. Although stem cell therapy for glaucoma treatment has yet to be comprehensively explored in clinical trials, preclinical studies reveal that stem cell therapy could be a promising treatment for glaucoma.…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Stem cells can ameliorate the RGC loss that occurs in glaucoma by differentiating into RGCs, integrating into the host retina, and secreting neuroprotective and anti-inflammatory factors [54 ▪ ,68,69 ▪ ,70–72]. Studies have shown that iPSC-derived RGCs can successfully integrate into the RGC layer [73,74 ▪ ,75 ▪ ], and embryonic stem cells (ESCs) can differentiate into functional RGCs and localize in the retina after transplantation in glaucoma animal models [76 ▪▪ ,77,78].…”
Section: Stem Cell Therapymentioning
confidence: 99%
“…Regeneration of RGCs requires full synaptic integration of host inner retinal stem cells and the development of long-distance axons, which project to the brain and accurately form effective synaptic connections with corresponding targets to complete signal transmission. Up to now, the replacement of RGCs has not made a breakthrough ( Zhang J. et al, 2021 ). Several recently studied cell types for transplantation including mouse induced pluripotent stem cell (miPSC) or mouse embryonic stem cell (mESC)-derived RGC ( Oswald et al, 2021 ) and spermatogonial stem cell-derived RGC ( Suen et al, 2019 ).…”
Section: Cell Therapymentioning
confidence: 99%